2022
DOI: 10.14218/erhm.2022.00052
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Dental Implants on the Circadian Clock and the Role of Melatonin in the Oral Cavity

Abstract: The circadian rhythm regulates many physiological human health and disease processes. The central circadian clock is located in the suprachiasmatic nucleus in the hypothalamus and controls a whole range of circadian clock genes. During bone remodeling, circadian rhythm gene expression was observed in osteoblasts and osteoclasts. Moreover, circadian rhythm genes are an essential part of the circadian network in the osseointegration of titanium implants. Namely, titanium biomaterials significantly affect the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…The circadian rhythm affects melatonin secretion [ 80 ], and the reduced secretion of melatonin leads to a decrease in antioxidants, which results in higher production of reactive oxygen species in saliva [ 54 ]. By decreasing antioxidants, including melatonin, the increased level of reactive oxygen species in saliva leads to changes in salivary oxidative biochemistry, which has been associated with the development of dental caries [ 81 ].…”
Section: Circadian Rhythmmentioning
confidence: 99%
“…The circadian rhythm affects melatonin secretion [ 80 ], and the reduced secretion of melatonin leads to a decrease in antioxidants, which results in higher production of reactive oxygen species in saliva [ 54 ]. By decreasing antioxidants, including melatonin, the increased level of reactive oxygen species in saliva leads to changes in salivary oxidative biochemistry, which has been associated with the development of dental caries [ 81 ].…”
Section: Circadian Rhythmmentioning
confidence: 99%
“…This pleiotropic hormone has several different functions [4], but regulating circadian rhythm, including sleep and wakefulness, is considered the most important one [5]. Previous studies confirmed its fundamental antioxidant effects since it scavenges free radicals and stimulates antioxidant enzymes and molecules to prevent radicals [6,7], besides having antiinflammatory and possibly epigenetic regulatory functions [8][9][10]. Melatonin's circadian rhythm of secretion [11], through increased secretion during the night and decreased secretion during the day, coordinates physiological processes and behavioral activities [2,3].…”
Section: Introductionmentioning
confidence: 99%